Pilot application of a novel nano-clay relative permeability modifier in a mature Malaysian offshore oilfield - Shafian, S.R.M. (Society of Petroleum Engineers, 2021)
Excessive water production associated with a decrease in hydrocarbon production is becoming a big challenge in matured offshore fields. Producing a barrel of water requires more energy that creates major economic impact on the profitability of an oil-field project. This paper presents a case study for water shut off treatment with a novel relative permeability modifier (RPM) (nano-clay). The nano-clay demonstrated high resistance to water flow (RRFw >10) and less effect to oil flow (RRFo <5) and capable to change the rock surface's wettability to more water wet. The main pilot objective was to assess the chemicals performance as part of production enhancement effort to reduce the water production from 90 to 50 water cut and to accelerate the oil production. We discussed the overall workflow, pilot execution, challenges and best practices including the laboratory results with the reference during research and development stage. The well treatment consists of bull-heading a pill of pre-flush of treated sea water for injectivity test, followed by nano-clay injection, post-flush with treated sea water, soaking for 48 hours and flow back the well. Pilot execution was completed successfully and safely within the target execution plan and are currently in monitoring stage. The post-treatment results and the overall economic success will then decide the future replication plan of this new water shut off technology. Â© 2021, Society of Petroleum Engineers.